2022
DOI: 10.7554/elife.77030
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive mechanisms of epilepsy-causing mutants discovered by measuring S4 movement in KCNQ2 channels

Abstract: Neuronal KCNQ channels mediate the M-current, a key regulator of membrane excitability in the central and peripheral nervous systems. Mutations in KCNQ2 channels cause severe neurodevelopmental disorders, including epileptic encephalopathies. However, the impact that different mutations have on channel function remains poorly defined, largely because of our limited understanding of the voltage sensing mechanisms that trigger channel gating. Here, we define parameters of voltage sensor movements in wt-KCNQ2 and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 65 publications
(94 reference statements)
2
11
0
Order By: Relevance
“…1A ) ( 7 , 8 , 37 , 41 ). Consistent with other studies ( 45 , 47 , 48 ), our VCF results showed that KCNQ3, unlike KCNQ1, exhibits a one-step VSD transition based on steady-state voltage-dependent activation ( Fig. 1, D and E ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…1A ) ( 7 , 8 , 37 , 41 ). Consistent with other studies ( 45 , 47 , 48 ), our VCF results showed that KCNQ3, unlike KCNQ1, exhibits a one-step VSD transition based on steady-state voltage-dependent activation ( Fig. 1, D and E ).…”
Section: Discussionsupporting
confidence: 93%
“…1D ). A recent VCF study of KCNQ2 showed a similar result ( 48 ). These results differ from the VCF recordings of KCNQ1, which exhibit two well-separated components in the F - V relation (F1 and F2) as the result of the two-step VSD activation ( Fig.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…In the current article, Edmond et al investigate biophysical properties of KCNQ2 to elucidate how different mutations alter channel function. 7 They used 2 methods to investigate the components that are involved in voltage sensing. In each case, mutated KCNQ2 channel proteins are expressed in oocytes for electrophysiological analysis.…”
Section: Commentarymentioning
confidence: 99%